Managing Insomnia Using Lucid Dreaming Training: A Pilot Study. Issue 2 (4th March 2021) - Ellis, Jason G.; De Koninck, Joseph; Bastien, Celyne H.
ABSTRACT: Objectives/Background : Despite Cognitive Behavioral Therapy for Insomnia (CBT-I) being considered the first-line treatment for insomnia, it is not without its challenges. As such it is worthwhile to consider, and test, alternative or adjuvant management options. Methods/Participants : The aim of the present study was to examine whether Lucid Dreaming Training for insomnia (LDT-I) impacted on insomnia, depressive and anxious symptomology in an open label trial of 48 adults with Insomnia Disorder. Participants completed the Insomnia Severity Index, General Anxiety Disorder-7 and Patient Health Questionnaire at baseline then one month following LDT-I. Training consisted of four modules delivered over a period of two consecutive weeks. Results : The results suggest, albeit preliminarily, that LDT-I may have a place within the non-pharmacological management of insomnia, as there were significant reductions in insomnia severity (t(46) = 8.16, p <.001), anxious symptomology (t(46) = 4.75, p <.001) and depressive symptomology (t(46) = 5.87, p <.001). Further, the effect size in terms of pre-post reductions on ISI scores was large (dz 1.17). Conclusions : Whilst the results are promising, further testing of LDT-I is needed to inform its place amongst the non-pharmacological treatments for insomnia.